2000
DOI: 10.1080/00288233.2000.9513439
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of New Zealand high‐country pastures under contrasting development inputs. 4. Organic matter components

Abstract: Biomass, N, S, P, C, and Ca composition of shoots, litter, roots and coarse organic matter > 1.3 mm diam., and <2 mm soil fraction are given for two trials under 61 different fertiliser and grazing treatments on a Pukaki/Tekapo high-country soil after 10-15 years. Effects were primarily related to fertiliser, secondarily to stocking rate, and rarely to the grazing method. While there was an increase in soil C and N and a decrease in C/N ratio of the <2 mm soil fraction with increasing fertiliser rate, the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…a P/S fertilizer). Previous studies from this study site showed that pasture growth responded to the addition of P and S, and that irrigation of fertilized plots strongly increased production (Scott 2000). A recent study (Lalibert e et al 2012b) showed that unfertilized plots were dominated by plants with a conservative nutrient-use strategy, whereas plants with leaf traits associated with rapid growth were more abundant in fertilized plots.…”
Section: Experimental Designmentioning
confidence: 61%
See 1 more Smart Citation
“…a P/S fertilizer). Previous studies from this study site showed that pasture growth responded to the addition of P and S, and that irrigation of fertilized plots strongly increased production (Scott 2000). A recent study (Lalibert e et al 2012b) showed that unfertilized plots were dominated by plants with a conservative nutrient-use strategy, whereas plants with leaf traits associated with rapid growth were more abundant in fertilized plots.…”
Section: Experimental Designmentioning
confidence: 61%
“…a P/S fertilizer). Previous studies from this study site showed that pasture growth responded to the addition of P and S, and that irrigation of fertilized plots strongly increased production (Scott ). A recent study (Laliberté et al.…”
Section: Methodsmentioning
confidence: 77%
“…Only the more closely fitting functions were pursued for the more inclusive analyses (ii, iii, and iv). The fit was also calculated for slightly more than half the data (780 observations) covering the zero fertiliser treatments and fertiliser combinations most likely to be economical (Scott 2000c). The mean deviation (Dev.)…”
Section: Alternative Fertiliser Response Functionsmentioning
confidence: 99%
“…Previous papers have described the trial designs and fertiliser levels used (Scott 1999), the changes in soil inorganic components after 10 years (Scott 2000a), sheep carrying capacities over 15 years (Scott 2000b), and organic components including pasture response (Scott 2000c). These could be considered as referring to a maintenance phase after an approximately five-year initial pasture development phase.…”
Section: Introductionmentioning
confidence: 99%
“…These interests have been particularly true for South Island high-country rangeland pastoral farming. The present series of papers attempts to quantify some of these production and sustainability aspects based on two long-running grazing pasture trials under contrasting management inputs of fertiliser and grazing management (Scott 1999(Scott , 2000a(Scott , 2000b(Scott , 2000c(Scott , 2000d.…”
Section: Introductionmentioning
confidence: 99%